Karakter Morfologi dan Kemampuan Silang Alami Tetua Padi Hibrida di Tiga Lokasi Berbeda - Widyastuti, Yuni; Wibowo, Bayu Pramono; Satoto, Satoto (Jurnal Penelitian Pertanian Tanaman Pangan, 2020)
Adoption of the hybrid rice varieties by farmers is often impaired by the high price of hybrid seed, due to low yields in hybrid seed production fields. Female outcrossing ability and female hybrid seed production ability, defined as the rate of filled spikelets of the male sterile line and as its grain yield under outcrossing, respectively, determine plant traits for hybrid seed yield. We identified an morphological characters and outcrossing rate ability of 6 hybrid rice combination that affect grain yield of hybrid rice seed production. The experiment conducted in 3 locations i.e. Subang, Malang, and Ungaran districts during dry season of 2016. Subang is the best location to hybrid rice seed production with the highest average of grain yield. Hipa 19 was the hybrid varieties having > 1 ton/ha grain yield highest that others. The important agronomic characteristics that affected of F1 grain yield i.e. plant height, number productive tillers, number of filled grains, exerted panicle rate, dan outcrossing rate. Correlations between number of filled grains, outcrossing rate, and grain yield were tight and highly significant. High yield potential and cost-effective for hybrid seed production can be achieved using hybrid rice with high outcrossing rate and suitable condition of an environment.